A new through-the-scope clip with anchor prongs is safe and successful for a variety of endoscopic uses - Guardiola, John J.; Rex, Douglas K.; Thompson, Christopher C.; Mosko, Jeffrey; Ryou, Marvin; Peetermans, Joyce; Rousseau, Matthew J; von Renteln, Daniel (Endoscopy International Open, 2024)
Background and study aims Endoscopic through-the-scope clips (TTSC) are used for hemostasis and closure. We documented the performance of a new TTSC with anchor prongs.Patients and methods We conducted a prospective case series of the new TTSC in 50 patients with an indication for endoscopic clipping at three hospitals in the United States and Canada. Patients were followed for 30 days after the index procedure. Outcomes included defect closure and rate of serious adverse events (SAEs) related to the device or procedure.Results Fifty patients had 56 clipping procedures. Thirty-four procedures were clipping after endoscopic mucosal resection (EMR) in the colon (33) or stomach (1), 16 after polypectomy, two for hemostasis of active bleeding, and one each for fistula closure, per-oral endoscopic myotomy mucosal closure, or anchoring a feeding tube. Complete defect closure was achieved in 32 of 33 colon EMR defects and 21 of 22 other defects. All clips were placed per labeled directions for use. In 41 patients (82.0%), prophylaxis of delayed bleeding was reported as an indication for endoscopic clipping. There were three instances of delayed bleeding. There were no device-related SAEs. The only technical difficulty was one instance of premature clip deployment.Conclusions A novel TTSC with anchor prongs showed success in a range of defect closures, an acceptable safety profile, and low incidence of technical difficulties.
Keywords: Endoscopy Lower GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...); Endoscopy Upper GI Tract; POEM; Gastrostomy and PEJ